Effects of the Consumption of Milk Biofortified with Selenium, Vitamin E, and Different Fatty Acid Profile on Immune Response in the Elderly. Issue 4 (15th January 2018) - Pfrimer, Karina; Ferriolli, Eduardo; Takeuchi, Paula Lumy; Salles, Márcia SV; Saran‐Netto, Arlindo; Zanetti, Marcus A; Roma‐Junior, Luiz C; Braga, Camila Bitu Moreno; Domenici, Fernanda A; Valim, Yara ML; Paschoalato, Adriana BP; Marchi, Larissa F; et al.
Abstract : Scope: Nutrition is a major contributing factor for immunocompetence. The aim was to assess the immune status of older people after consuming milk produced by lactating cows fed with one of the following diets: control diet (C), C + vitamin E + selenium (C + A), C + sunflower oil (C + O), and C + sunflower oil + vitamin E + selenium (A + O). Methods and results: Sixty elderly people received one of these biofortified milks for 12 weeks. Immune response was assessed by measurement of the expression of COX‐1, COX‐2, MCP‐1, PPAR (δ, α, and β/δ) genes, neutrophil production of oxygen reactive species induced by immune complexes, neutrophil phagocytosis and lytic activity of the alternative pathway of the complement system, and cytokine levels. Variables were assessed before and after treatment. Our findings showed stability of some inflammatory mediators (complement activity and neutrophils burst) in treatment groups, except complement activity in C + A, and an increase of these markers in C, especially reactive oxygen species production and phagocytic activity. TNF‐α was significantly increased in all groups. In C + A, IL‐4 and IL‐2 increased after treatment, and in the group that received the milk produced by cows fed with "O" diet, CCL20 and IL‐27 increased. Conclusion: Overall, as compared to C, milk biofortification was associated with stabilization of the activity of alternative complement pathway and the neutrophils burst, and modulated different cytokines levels. Abstract : In this study, milk is biofortified through the supplementation of cows' ration with selenium, vitamin E, and sunflower oil. The use of the biofortified milk alters the immune response (complement activity and neutrophils burst) of institutionalized older people.